“I hardly have a problem […] I have my period quite rarely too”: Female football players’ and their coaches’ perceptions of barriers to communication on menstrual cycle - Bergström, Max; Rosvold, Malene; Sæther, Stig Arve (Frontiers in Sports and Active Living, 2023)
Introduction Symptoms related to the menstrual cycle (MC) affect the performance level and health of female athletes in various ways. Previous research has reported MC symptoms such as pain, mood disturbance, reduced coordination and competition distraction as well as diminished performance levels and an increased injury risk among female elite athletes. Despite this, the coach-athlete communication related to the female hormonal cycle is limited. The aim of the present study was to explore the perceptions of MC communication in a group of junior elite football players and their male coaches in a case study of one youth football team in a specific club in Norway. Methods The study used a qualitative approach with semi-structured interviews. In total, 8 female junior elite players (aged 16-20) from a Norwegian football team and 2 of their male coaches participated in the study. Results The data analysis revealed two main communication barriers: 1. interpersonal barriers (e.g., false assumptions about the coach/athletes and social discomfort) and 2. knowledge barriers (e.g., unaware/perceptions of insufficient knowledge levels). Discussion As the players seemed to be unaware of their insufficient MC knowledge (e.g., failed to see a connection between the MC and their health and performance level), the coaches perceived their knowledge as insufficient and coped mainly by outsourcing MC communication to female staff and apps. Hence, the MC communication was hindered by both the athletes and the coaches (e.g., mutual avoidance). In line with previous research, this study supports that there is a need for developing effective strategies to overcome the interpersonal barriers and knowledge gaps.